Geological features based on Spectral Decomposition: Techniques and examples from the Malay Basin - Shamsuddin, A. (Institute of Physics Publishing, 2017)
Seismic resolution is of interest in exploration and production of hydrocarbon area as it may hinder geological understanding. A frequency study-spectral decomposition was implemented in order to enhance geological understanding in the study area as it is related to the seismic resolution. Spectral Decomposition based on Fourier Transform analysis was conducted in the study area which is located in the Malay Basin. Four geological features were determined in the analysis 1 and three geological features were determined during analysis 2. The thickness and appearance of the geological features such as sharp edges, discontinuity were detected based on this analysis. The abandoned channel can be identified in the southeast part of the study area and was detected based on the modulation of the spectral decomposition analysis. © Published under licence by IOP Publishing Ltd.